Toward More Inclusive Work Organizations by Redesigning Work - Mulders, Henny; van Ruitenbeek, Gemma; Wagener, Bert; Zijlstra, Fred (Frontiers in Rehabilitation Sciences, 2022)
Inclusive Work Redesign (IWR) is an innovative strategy to create feasible job opportunities for job seekers from vulnerable groups at the labor market, in particular people with disabilities, in such a way that it contributes to sustainable employment for all staff and to the organization’s performance. As an element of active labor market policies (ALMP), in the Netherlands, IWR is used as an instrument for Public Employment Services (PES) and professionals in occupational rehabilitation to support employers, using a demand-oriented approach. IWR is also a potential valuable asset for strategic human resource management (SHRM) aimed at inclusion and sustainable employment. The article describes IWR in the context of social security and staffing problems of organizations, and the application of IWR in the Netherlands and Germany.